Analisis Strategi Pemasaran Untuk Meningkatkan Daya Saing Pada UMKM Rumah Makan Ibu Lili - Erlin Kusuma; Yacobo Perdamaian Sijabat (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
The marketing strategies is one of way to win a sustainable competitive advantage both for companies that produces goods or services. The marketing strategies can use as a basic in order to preparing of the companies planning. As a views from the problems which are exists in the company. So it is necessary to comprehensive plans to be used as guideline of the segments company in carrying out its activities, the other reasons that demonstrates the importance of marketing strategy is increasingly tough competition the company in general. This study aims to: obtain an overview of the marketing strategies used by MSMEs Rumah Makan Ibu Lili improve its competitiveness and to determine how effective implementation of marketing strategies. The experiment was conducted in MSMEs Rumah Makan Ibu Lili at Borobudur. Data collection methods used in this study is documentation, interview, observation and descriptive research. The results of an analysis of the effectiveness of the marketing strategies showed the increased of total sales of year to year and became references the marketing strategies in competitions between traditional food companies.